Geometrical Shape Investigation for Electrodes in Silent Discharge Chamber - Mochammad Facta; Ngurah Ayu Ketut Umiati; Agung Warsito (IAES Indonesia Section, 2016)
Silent discharge is the most prominent method to carry out plasma reaction because. discharge is easily initiated by injecting alternating current in high voltage to the pair of separated electrodes. The electron emission from surface of dielectric placed on instantaneous cathode is stimulated by ion induced electron emission. In this method, spark is avoided by placing insulation material to either one or both of the electrodes. In practical, it is very difficult to determine the exact limit of the voltage that initiate the discharge by mathematical analysis because it depends on many factors, namely dimensions, type and geometrical shapes of electrode, thickness of insulation, and type of electric field inside the discharge gap. To get lower initial voltage for discharge, it is important to find the best geometrical shape of electrode in relation to skin effect that trigger electron emission. This work investigates the behaviour of charges, current, electric field and voltage surrounding electrodes with various geometrical shape.Silent discharge is the most prominent method to carry out plasma reaction because. discharge is easily initiated by injecting alternating current in high voltage to the pair of separated electrodes. The electron emission from surface of dielectric placed on instantaneous cathode is stimulated by ion induced electron emission. In this method, spark is avoided by placing insulation material to either one or both of the electrodes. In practical, it is very difficult to determine the exact limit of the voltage that initiate the discharge by mathematical analysis because it depends on many factors, namely dimensions, type and geometrical shapes of electrode, thickness of insulation, and type of electric field inside the discharge gap. To get lower initial voltage for discharge, it is important to find the best geometrical shape of electrode in relation to skin effect that trigger electron emission. This work investigates the behaviour of charges, current, electric field and voltage surrounding electrodes with various geometrical shape.